PENGARUH MOTIVASI, DISIPLIN KERJA DAN SEMANGAT KERJA TERHADAP KINERJA KARYAWAN PADA PT. PEMBANGUNAN ABADI ANDALAS AGUNG DI KOTA DURI, RIAU - Hasibuan Mutiah Elma; Marnis Marnis; Pramadewi Arwinence (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine simultaneously and partially the influence of motivation,work discipline, and morale on the performance of employees at PT. PembangunanAbadi Andalas Agung Duri, Riau. The population in this study amounted to 35 people. Inthis study, the census method was used, the entire population was sampled. The types ofdata used in this research is primary and secondary data. The data collection techniqueis a questionnaire. Hypothesis testing in this study using multiple linear regression testwith t-test, F-test and coefficient of determination. The data collected was first analyzedby testing the quality of the instrument, classical assumption test and hypothesis testingusing SPSS version 23 test tool. The results of this study indicate that: (1) Motivation,Work Discipline and work Morale simultaneously have a significant effect on employeeperformance. (2) Motivation partially has a significant effect on employee performance.(3) Work Discipline partially has a significant effect on employee performance. (4) Workmorale partially has a significant effect on employee performance. Keywords : Motivation, Work Discipline, Morale and Employee Performance